2021
DOI: 10.1051/e3sconf/202125601040
|View full text |Cite
|
Sign up to set email alerts
|

Position Sensorless Control of Switched Reluctance Motor under Magnetic Field Saturation

Abstract: When the switched reluctance motor is running, as the motor phase current increases, the magnetic circuit of the motor will gradually saturate, which affects the estimation of the special position of the motor rotor. Aiming at the above problems, this paper proposes a positionless control method for switched reluctance motors under the condition of magnetic field saturation. Firstly, the Fourier phase inductance function of switched reluctance motor is established, and then the component of Fourier phase induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…This formula (6) shows that in addition to being related to the position angle error, the number i qin also has a relationship by modulating the signal sinωt, and it is related to its change over time as well. According to the following strategy, signals on the q-axis indicating high-frequency currents should be extracted by means of the following procedure.…”
Section: Rotor Position Estimation Based On the Pll Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…This formula (6) shows that in addition to being related to the position angle error, the number i qin also has a relationship by modulating the signal sinωt, and it is related to its change over time as well. According to the following strategy, signals on the q-axis indicating high-frequency currents should be extracted by means of the following procedure.…”
Section: Rotor Position Estimation Based On the Pll Techniquementioning
confidence: 99%
“…A positionless system block diagram is shown above for the PLL-based pulsed high-frequency voltage injection system being described above. The system model can be established under a MATLAB/Simulink environment .In the simulation, the following parameters of the motor were included for reference:number of pole pairs P n =2; stator inductance L d =0.00473H, L q =0.009H; stator resistance R=0.45Ω; flux linkage ψ f =0.683Wb; rotational inertia J=0.008 Kg*m 2 [6] . It can be observed that in the simulation time of 4 seconds, the pulsed high-frequency voltage signal is 15V in amplitude and the frequency is 1000Hz [7] .…”
Section: Simulation Studymentioning
confidence: 99%